Job insecurity, union involvement and union activism - De Witte, Hans (Aldershot, 2005)
"This volume contains empirical analyses of European psychologists and sociologists on the impact of job insecurity on trade union membership, activism and upon the attitudes of individual workers towards unions. Little is currently known about the impact of job insecurity on the union participation of workers, which is significant given the importance of trade unions in European collective bargaining systems. This volume reports innovative and pioneering research on this research gap. It answers questions such as: do workers more easily join unions because of job insecurity, or does it make them leave the union? Does it influence participation in work's council elections or affect the intention to become a union activist? And are workers less satisfied and less committed to their unions when they experience job insecurity? The book contains recommendations for policy makers, social partners and practitioners in the field of work and organizations."